Developmental outcome of babies born to mother infected with Coronavirus-19 during pregnancy - Ojha, Anil Raj; Bartaula, Bikalpa (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Developmental effect on children of mothers who had corona virus during pregnancy is unknown. This study aims to determine developmental outcomes of these babies after infancy. Method: This is an observational study carried out from 1 Oct 2020 to 31 Dec 2020. All the babies born from the mother who were tested positive for coronavirus anytime during pregnancy were included. Controls were those babies whose mothers were PCR negative prior to delivery. All the children were assessed for development at 12 months of age . They were screened using BRIGANCE III and ages and stages questionnaires (ASQ) for development profile in all domains. The total score obtained in the test was compared against the normative value for that age and sex. Result: During the study period 1967 babies were delivered. Among them 48(2.44%) babies were born from mothers who were tested positive for COVID-19. Out of these 12 children returned for development assessment. Out of 12 cases two (16.6%) and among controls three (25%) failed the BRIGANCE III screening. This difference is not statistically different (p=0.61). ASQ showed that among all the cases who failed developmental screening test, in both groups, were below cut off score in communication domain. Conclusion: There is no difference in the developmental outcome of children who were born from a mother who contracted COVID-19 during pregnancy as compared to those born from mothers who had no evidence of that infection.